Laser Lithotrpsy of Large Choledochal Stones - Ali Erkan Duman; Emrah Gülşen (Diagnostic and Interventional Endoscopy)
Objective: The purpose of laserlithotripsy accompanied bycholangioscopy is to break the Stones into smaller pieces that form in the bile ducts and cannot be removed by conventional methods.This procedure is performed to relieve obstruction of the bile ducts and enable easier removal of stones. Since it is a minimally invasive method, the recovery time is shorter.